Interaction between serotonin and dopamine and impulsivity: A gene × gene - interaction approach. (1st February 2021) - Hennig, Juergen; Netter, Petra; Munk, Aisha J.L.
Abstract: While large consensus exists concerning the relationship between low serotonin (5-HT) activity/functionality and high impulsivity, the kind of involvement of dopamine is less clear. We used a molecular genetic approach to demonstrate that 5-HT modulates the relationship between DA and impulsivity on the level of functional candidate genes coding both, the serotonin transporter (SERT, SLC6A4) and the dopamine transporter (DAT, SLC6A3). A number of 660 male and female students (Caucasians) were genotyped for the 5-HTTLPR and the DAT1-VNTR polymorphisms and completed the Multidimensional Personality Questionnaire (MPQ-BF). The results indicate that 5-HTTLPR and DAT1-VNTR, as well as the interaction between both of them, relate to the broader factor "constraint". The main effect of 5- HTTLPR and the interaction with DAT1-VNTR can also be obtained for "control". The combination of s-allele (5-HTTLPR) and homozygous 9R-allele (DAT) resulted in the highest impulsivity whereas carriers of the homozygous l-allele in combination with the homozygous 9R-allele exhibited the lowest levels. Neither main effects nor interaction-effects could be observed for the two subscales "traditionalism" and "harmavoidance". Results are discussed concerning the usefulness of the candidate gene approach by the use of theory driven gene × gene interactions and the implication for impulsivity in health and disease.